Which precocial rodent species is more suitable as the experimental model of microgravity influence on prenatal musculosketal development on international space station?. (May 2022) - Sekulic, Slobodan; Jovanovic, Aleksandar; Zivanovic, Zeljko; Simic, Svetlana; Kesic, Srdjan; Petkovic, Branka; Capo, Ivan; van Loon, Jack JWA
Abstract: The International Space Station (ISS) has the possibility to perform experiments regarding rodent reproduction in microgravity. The musculoskeletal system at birth in precocial rodent species more resembles the human than that of altricial rodent species. For precocial rodent species with body weight ≤ 500 g (limit of ISS) determined were: adult body mass, newborn body mass, head-body length, tail length, existing variants (wild, domesticated, laboratory), single/group housing, dry food consumption/24 h, water intake/24 h, basal metabolic rate mlO2/g/h, environmental temperature, sand baths, urine output ml/24 h, fecal output g/24 h, size of fecal droplet, hair length, life span, length of oestrus cycle, duration of pregnancy, building nest, litter size, stage of musculoskeletal maturity at birth, and the duration of weaning. Characteristics were obtained by searching SCOPUS as well as the World Wide Web with key words for each of the species in English, Latin and, local language name. These characteristics were compared in order to find most appropriate species. Twelve precocial rodent species were identified. There is not enough data for Common yellow-toothed cavy, and Eastern spiny mouse. Inappropriate species were: Gundis, Dassie rat are a more demanding species for appropriate tending, litter size is small; Octodon degus requires sand baths as well as a nest during the first two weeks after delivery; muscle maturity of Spiny mouse at birth (myotubular stage), does not correspond to the human (late histochemical stage); Chinchilla requires separately housing, daily sand baths, has upper limit of weight. Possibility of keeping Southern mountain cavy as pet animal, short estrus, large litter size, absence of the need for nest and sand baths, makes this species the most promising candidates for experiments on ISS. If an experiment is planned with exposing gravid animals before term of the birth, then they might be kept together in the existing Rodent Habitat (USA). If an experiment with birth in microgravity is planned on ISS, the existing habitats do not provide conditions for such an experiment. It is necessary to develop habitats for separate keeping of pregnant animals to enable the following: 1. undisturbed delivery 2. prevent the possibility of hurting the newborns 3. ensure adequate post-partum maternal care and nursing.